Economic Value of Carbon Sequestration in Telaga Warna National Park - Esap Mundi Hartono (School of Postgraduate Studies, Diponegoro Univer, 2025)
Forests are crucial natural resources in Indonesia, storing significant biodiversity and providing essential benefits for both the environment and people's livelihoods. They contribute significantly to the country's economy, support local communities, and play a vital role in mitigating climate change through carbon sequestration. The economic value of carbon sequestration in Telaga Warna National Park, holds significant importance in understanding the role of forests in mitigating climate change and fostering sustainable development. This study explores the carbon storage potential within the park's tree forests and assesses its for economic value. The research conducted in Telaga Warna National Park revealed a rich diversity of plant species within the ecosystem. Specifically, the study concentrated on two distinct categories of plants: pole plants, characterized by diameters ranging from 10 cm to 19.9 cm, and trees, distinguished by diameters larger than 20 cmTelaga Warna National Park, located in West Java, Indonesia, is renowned for its biodiversity and ecological significance, making it an ideal site for studying carbon sequestration dynamics. The data was collected within a subplot measuring 10x10 meters, and for trees within a plot measuring 20x20 meters. Based on the data obtained, it is found that the dominant vegetation in Telaga Warna National Park is Riung Anak / Casitanopsis javanica, and a potential carbon value of Telaga Warna is US 2.96 per Ha for pole species and US 98.49 for tree species. In conclusion, the economic value of carbon sequestration in Telaga Warna National Park underscores the critical role of forests in addressing global environmental challenges